Kryptosammensætninger og skabsafledninger i virkeligheden og i ordbøgerne - Jarvad, Pia (Nordiske Studier i Leksikografi, 1995)
In the paper I discuss the borderline between compounding and derivation exemplified by new words as skabsbøsse 'closet queen', teflonpolitiker 'teflon politician' and eurokrat 'Eurocrat', økotrend 'ecological trend'. I suggest the terms kryptosammensætning (crypto-compound) and skabsafledning (pseudo-derivation) for the results of a word formation created by highly productive elements which are traditionally regarded as affixes or roots but have a function as roots or affixes. The two types are described in present day vocabulary and compared with the treatment of them in two dictionaries.